Open access, open education resources and open data in Uganda - Ivana, Di Salvo; Mwoka, Meggie; Kwaga, Teddy; Rukundo, Priscilla Aceng; Ssesanga, Dennis Ernest; Osaheni, Louis Aikoriogie; Kasibante, John; Kasirye, Shafik; Agostinho, Moreira de (Pan African Medical Journal, 2015)
As a follow up to OpenCon 2014, International Federation of Medical Students' Associations (IFMSA) students organized a 3 day workshop Open Access, Open Education Resources and Open Data in Kampala from 15-18 December 2014. One of the aims of the workshop was to engage the Open Access movement in Uganda which encompasses the scientific community, librarians, academia, researchers and students. The IFMSA students held the workshop with the support of: Consortium for Uganda University Libraries (CUUL), The Right to Research Coalition, Electronic Information for Libraries (EIFL), Makerere University, International Health Sciences University (IHSU), Pan African Medical Journal (PAMJ) and the Centre for Health Human Rights and Development (CEHURD). All these organizations are based or have offices in Kampala. The event culminated in a meeting with the Science and Technology Committee of Parliament of Uganda in order to receive the support of the Ugandan Members of Parliament and to make a concrete change for Open Access in the country.